Does the Infestation by Trematode Parasites Influence Trade-Offs Between Somatic Condition and Male Reproductive Traits in a Viviparous Fish? - Domínguez-Castanedo, Omar (Journal of fish diseases, 2025)
© 2024 The Author(s). Journal of Fish Diseases published by John Wiley & Sons Ltd.